PO92 | Challenging management of portal vein thrombosis in a cirrhotic patient on hormone therapy after breast cancer (Bleeding, Thrombosis and Vascular Biology)
Background: Portal vein thrombosis (PVT) is a multifactorial condition frequently associated with liver cirrhosis, malignancies, or prothrombotic states. In cirrhotic patients, reduced portal flow, endothelial dysfunction, and systemic inflammation can promote thrombosis even in the absence of documented thrombophilia. Hormonal therapy, particularly in hormone-sensitive breast cancer, may further increase thrombotic risk. Anticoagulation in cirrhotic patients with thrombocytopenia remains controversial, often limited by drug intolerance and bleeding risk.